Do Pharyngeal Surgeries for Snoring and Obstructive Sleep Apnea Have an Impact on Nasalance Scores?. Issue 7 (October 2015) - Karakoc, Omer; Akcam, M. Timur; Genc, Hakan; Birkent, Hakan; Binar, Murat; Gerek, Mustafa
Abstract : Objective: Most of the surgeries which are used in the treatment of habitual snoring and obstructive sleep apnea (OSA) mainly target velopharyngeal structures, which play an important role in voice characteristics such as nasalance. The aim of this study is to assess the effect of different types of such surgical procedures including expansion sphincter pharyngoplasty (ESP), lateral pharyngoplasty (LP), and anterior palatoplasty (AP) on nasalance scores. Subjects and Methods: Forty-nine consecutive patients with primary snoring or OSA who underwent AP, LP, and ESP procedures were included in this study. All patients underwent a fully attended overnight polysomnography and detailed otolaryngologic examination. Nasalance studies were performed with Nasometer II instrument (model 6400; Kay Elemetrics, Lincoln Park, NJ) by reading 3 passages that were categorized according to the amount of nasal consonants (oral, oro-nasal, and nasal passages), preoperatively, and 3 months after surgery. Results: There was no statistically significant difference in either group between preoperative and postoperative assessments of nasalance scores for all 3 passages. Seven patients experienced nasal regurgitation symptoms for fluids for a short time after LP, 2 patients after AP, and 7 patients after ESP. None of these symptoms showed persistence and diminished approximately at 1-month follow-up. Conclusion: Anterior palatoplasty, LP, and ESP seem not to have any impact on nasalance scores of males.